2013
DOI: 10.1007/s12663-013-0472-0
|View full text |Cite
|
Sign up to set email alerts
|

Transoral Removal of Peripheral Osteoma at Sigmoid Notch of the Mandible

Abstract: Osteoma is a benign osteogenic slow-growing tumor. Though mandible is involved more often than the maxilla only one other case of osteoma sigmoid notch has been mentioned in the English literature till date. Cosmesis and function are the main reasons that dictate the removal of the osteomas, so we preferred to use an intra oral approach to better prevent the scar and achieve good patient acceptance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 8 publications
0
7
0
2
Order By: Relevance
“…Different imaging modalities like occlusal and panoramic radiographs, Waters view, computerized tomography (CT), magnetic resonance imaging (MRI), or CBCT can be used for the radiographic examination of POs (28). It is reported that POs in the craniofacial region are best visualized and localized by means of CT (29,30). In most of the cases in the literature the radiographic examination of the osteoma was performed with CT (14)(15)(16)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Different imaging modalities like occlusal and panoramic radiographs, Waters view, computerized tomography (CT), magnetic resonance imaging (MRI), or CBCT can be used for the radiographic examination of POs (28). It is reported that POs in the craniofacial region are best visualized and localized by means of CT (29,30). In most of the cases in the literature the radiographic examination of the osteoma was performed with CT (14)(15)(16)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ] The recurrence rate of osteoma is very rare. [ 20 ] Osteoma are believed to be relatively uncommon and most of them are compact variety[ 6 7 8 9 12 14 17 18 19 20 21 22 ] and cancellous type of osteoma is very rare. [ 2 3 5 11 23 ] Our patient of peripheral cancellous osteoma recovered without any complication after surgery, and there was no evidence of recurrence during 2 years of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Sigmoid notch osteomas are rare and to the best of our knowledge, this is only the sixth such case reported in English literature. [ 1 3 4 5 6 ] Among the previously reported cases [ Table 1 ], the mean age of presentation was 51 years. In contrast to the lateral location of the osteoma in our case and that reported by Bessho et al [ 1 ] and Rao et al ,[ 6 ] the others were in the middle[ 4 ] or the medial aspect of the sigmoid notch.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 3 4 5 6 ] Among the previously reported cases [ Table 1 ], the mean age of presentation was 51 years. In contrast to the lateral location of the osteoma in our case and that reported by Bessho et al [ 1 ] and Rao et al ,[ 6 ] the others were in the middle[ 4 ] or the medial aspect of the sigmoid notch. [ 3 5 ] Conservative management was adopted in cases where the lesion was asymptomatic; in this case progressive enlargement of the lesion and facial asymmetry warranted surgical excision.…”
Section: Discussionmentioning
confidence: 99%